Meta-Analysis the Effect of Residence on the Risk of Anxiety and Depression in General Population during COVID-19 Pandemic - Riyesti Hero Fresna; Bhisma Murti; Hanung Prasetya (Journal of Epidemiology and Public Health, 2021)
Background: The area of residence is one aspect that affects a person's mental health, especially during the COVID-19 pandemic. The difference in the area of residence determines the frequency of exposure to pandemic information in the form of valid invalid information which is increasingly massive, so that between urban and rural areas there can be a potential risk of depression and anxiety. This study aimed to analyze the effect of residence on the risk of anxiety and depression in the population during the COVID-19 pandemic.Subjects and Method: The meta-analysis was performed by searching for articles from Google Scholar, Pubmed, and ScienceDiret. The keywords used in the article search were